Pelatihan Berbasis Skill Rajutan Konektor Masker Terhadap Ibu-ibu Rumah Tangga Terdampak Covid-19 di Desa Tarai Bangun - Aslati Aslati; Silawati Silawati; Muhlasin Muhlasin (MENARA RIAU, 2022)
The Covid-19 pandemic has an impact on all aspects of people's lives, especially the economic impact. This condition is most affected by the household sector of mothers. Therefore, it is necessary to hold community service in the form of practical training by providing skills with the aim that certain skills can generate the family economy. The mentoring approach method uses a Socio-Economic approach, namely providing productive technical skills. The results of the mentoring activity in the form of training were 20 participants consisting of housewives and teenagers. The service team brought in one training instructor. The event started with providing counseling and motivational materials by one of the service teams, followed by the practice of making knitted mask connectors and the media had been prepared in advance. Participants were divided into two sessions, namely morning before noon and afternoon until afternoon. At the end of the activity, participants can produce knitted mask connectors that can be used alone and of course these skills can be of economic value in helping the family economy.